2016
DOI: 10.1007/s10735-016-9687-y
|View full text |Cite
|
Sign up to set email alerts
|

Wnt5a mediated canonical Wnt signaling pathway activation in orthodontic tooth movement: possible role in the tension force-induced bone formation

Abstract: Orthodontic tooth movement (OTM) is associated with bone remodeling mediated by orthodontic mechanical loading. Increasing studies reported that Wnt signaling played crucial roles in mechanical stimuli induced bone remodeling. However, little is known about the involvement of Wnt signaling in orthodontic force-induced bone formation during OTM. In virtue of the OTM mice model as we previously reported, where new bone formation was determined by micro-CT and immunoreactivity of osteocalcin and osterix, we explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 61 publications
4
40
0
1
Order By: Relevance
“…Although it has been well established that the canonical Wnt/β‐catenin signaling is of great importance for mechanosensation and mechanotransduction in osteogenic commitment of osteocytes, there still exists limited evidence with regard to the involvement of Wnt signaling in the orthodontic force‐induced osteogenic differentiation of PDLCs. It was found that when subjected to stretch force during OTM in murine model, the nucleus translocation of β‐catenin was distinctly increased in the PDLCs at the tension side of periodontium, which contributes to novel bone formation . On the other hand, in vitro study reported that β‐catenin may also serve as the effector of compressive loading in PDLCs .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been well established that the canonical Wnt/β‐catenin signaling is of great importance for mechanosensation and mechanotransduction in osteogenic commitment of osteocytes, there still exists limited evidence with regard to the involvement of Wnt signaling in the orthodontic force‐induced osteogenic differentiation of PDLCs. It was found that when subjected to stretch force during OTM in murine model, the nucleus translocation of β‐catenin was distinctly increased in the PDLCs at the tension side of periodontium, which contributes to novel bone formation . On the other hand, in vitro study reported that β‐catenin may also serve as the effector of compressive loading in PDLCs .…”
Section: Discussionmentioning
confidence: 99%
“…It was found that when subjected to stretch force during OTM in murine model, the nucleus translocation of β-catenin was distinctly increased in the PDLCs at the tension side of periodontium, which contributes to novel bone formation. 31 On the other hand, in vitro study reported that β-catenin may also serve as the effector of compressive loading in PDLCs. 16 Consistently, we confirmed the activation of the 33 In the present study, depletion of TAZ using siRNA offset the CTS-induced osteogenic differentiation and Wnt-related protein expressions, indirectly suggesting that TAZ could be the upstream element of Wnt/β-catenin signaling in the process of CTS osteogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In mice subjected to tooth movement via and open-coil spring, Lrp5 and Fzd4 (a Wnt co-receptor) were upregulated in the periodontium near alveolar bone. 20 In addition, the downstream canonical mediator β-catenin was also activated in the same tissues by tooth movement. Moreover, Lrp5-HBM mice exhibit an increase in alveolar bone formation, and narrowing of the PDL space.…”
Section: Wnt-med Iated S I G Nalling In Orthodonti C Tooth Movementmentioning
confidence: 99%
“…However, accumulating data suggests that Wnt signalling is also important in alveolar bone for tooth movement. In mice subjected to tooth movement via and open‐coil spring, Lrp5 and Fzd4 (a Wnt co‐receptor) were upregulated in the periodontium near alveolar bone . In addition, the downstream canonical mediator β‐catenin was also activated in the same tissues by tooth movement.…”
Section: Wnt‐mediated Signalling In Orthodontic Tooth Movementmentioning
confidence: 99%
“…The findings include regulation of pulp volume and dentin thickness [110], enhancement of dentin regeneration [111], and cementum regeneration [112]. Tooth movement during orthodontic treatment has also been shown to involve activation of Wnt signaling [113,114]. All of these have been shown to involve the Wnt signaling pathway.…”
Section: Further Development Pathsmentioning
confidence: 99%